Theology and Christian discipleship - O’Loughlin, Thomas (Dominican Publications, 2017)
Consists of 5 parts, every part publishes under separate title. Part 1. What is ‘God’? Doctrine and Life, vol. 67, number 9, September 2017, pp. 3-7 Part 2. Are We Short of Priests?Doctrine and Life, vol. 67, number 10, December 2017, pp. 16-19 Part 3. Can We Share a Table? Doctrine and Life, vol. 68, number 1, January 2018, pp. 18-22 Part 4. Does the Spirit Speak in Every Heart? Doctrine and Life, vol. 68, number 2, February 2018, pp. 29-31 Part 5. Are People Really ‘Not Religious’? Doctrine and Life, vol. 68, number 3, March 2018, pp. 26-29.